Transient transport of heat, mass, and momentum in paperboard including dynamic phase change of water. (December 2016) - Askfelt, Henrik; Alexandersson, Marcus; Ristinmaa, Matti
Abstract: A theory to describe deforming moist paperboard in environments where both temperature and pressure change significantly during a short period of time is presented. Paperboard is viewed as an orthotropic triphasic porous medium consisting of fibers, bound water and moist air. Furthermore, the moist air is considered as a mixture of two miscible gases, namely dry air and water vapor. A two–scale hybrid mixture theory is adopted in a large strain setting and balances of mass, linear momentum, and energy are presented on the macroscale. Constitutive relations are derived on the macroscale through exploitation of the dissipation inequality. Mass exchange between bound water and water vapor is included as a dynamic process. Mass transportation processes include chemical potential driven diffusion and nonlinear seepage flow. The elasto–plastic stress–strain response of the fiber network is described by assuming a multiplicative split of the deformation gradient associated with the motion of the fiber network. The dynamics related to the mass exchange between bound water and water vapor is illustrated by changes of pressure, relative humidity, moisture ratio, and rate of evaporation during rapid heating of a moist paperboard.